Aksi Bela Islam: islamic clicktivism and the new authority of religious propaganda in the millennial age in Indonesia - Muzayyin Ahyar; Alfitri Alfitri (Indonesian Journal of Islam and Muslim Societies, 2019)
The great Islamic mass rally which well known as “Aksi Bela Islam (Defending Islam action) 212” in Indonesia has always been claimed as the triumph of Islamic activism. This action continue to be voiced through social media such as Facebook, Twitter, Instagram, and so forth with the jargon “ 212 spirit “. The voluminous actions of “Aksi Bela Islam 212” sound like an authoritative propaganda jargon which are exhaled to spread the Islamic identity through the internet. Along with the proliferation of online Islamic activism, some major questions emerge about: (1) whether online religious discourse is an authoritative source that gives Muslim society an authority in religious propaganda; (2) to what extent the proliferation of online Islamic activism has shaped the new Islamic propaganda authority? The objective of this article is to examine the discourse of Islamic activism in the online public sphere which makes the internet and online social media as a new vehicle in the transformation of traditional-modern Islamic propaganda authority for technologically literate generation. The article highlights some transformations of traditional religious propaganda authority to the new one which appropriated with the technological advancement. Using political sociology approach, this article will maps an Islamic online activism, which is termed as Islamic clicktivism, and its relation to the religious propaganda authority. The finding of this article reveals that Islamic clicktivism can be an authoritative method in shaping religious and political discourses. Finally, this article argues that Islamic social movement in the millennial age – especially in the post 212 movement – has consistency to play a role in political contestation through the Islamic clicktivism. Gerakan aksi masal Islam yang dikenal dengan Aksi Bela Islam di Indonesia selalu diklaim sebagai kemenangan aktivisme Islam. Menyusul Aksi Bela Islam dalam ranah gerakan sosial, wacana serupa juga disuarakan melalui gerakan aktivisme secara daring yang disebarkan melalui berbagai media social seperti Facebook, Twitter dan Istagram dengan jargo “spirit 212”. Aksi berjilid-jilid dari Aksi Bela Islam ini terdengan seakan menjadi jargon propaganda otoritatif yang dihembuskan untuk menyebarkan identitas Islam melalui internet. Seiring dengan fenomena proliferasi gerakan-gerakan Islam daring tersebut, beberapa pertanyaan muncul: pertama, apakah diskursus keagamaan daring menjadi sumber otoritatif yang memberikan otoritas kepada masyarkat Muslim dalam hal propaganda agama? Kedua, sejauh mana proliferasi aktivisme Islam daring membentuk otoritas propaganda keagamaan baru? Sasaran dari artikel ini adalah menguji wacana aktivisme Islam di ruang public daring yang menjadikan internet dan media social daring sebagai kendaraan baru dalam transformasi otoritas propaganda keagamaan dari tradisional ke modern bagi kalangan melek milenial yang melek teknologi. Artikel ini menyoroti beberapa trasnformasi propaganda keagamaan tradisional menuju modern yang disesuaikan dengan perkembangan teknologi. Dengan menggunakan pendekatan sosiologi-politik, artikel ini memetakan aktivisme Islam daring, yang diistilahkan dengan Islamic clicktivism, dan hubungannnya dengan otoritas propaganda keagamaan. Temuan artikel ini menunjukkan bahwa kliktifisme Islam dapat menjadi metode otoritatif dalam membentuk wacana keagamaan dan politik sekaligus. Pada akhirnya artikel ini menegaskan bahwa gerakan social Islam di era milenial – khususnya pasca gerakan 212 –secara konsisten mengambil peran dalam kontestasi politik identitas dengan menggunakan kliktifisme Islam.